COMPENSATORY GROWTH IN BROILER CHICKEN (Gallus gallus domesticus) UNDER DIFFERENT FEEDING REGIMEN - P. Oraye, Venus Mae; Nicaile V. Malto (International Journal of Multidisciplinary Research and Studies, 2023)
To avoid rapid growth, boost weight gain while using less feed, and improve feed utilization, restriction—slowing broiler growth at early stages—was examined. An experiment with a completely randomized design was conducted to ascertain compensatory growth in broilers under varied feeding regimens: T1-Control, T2-10% Restriction, T3-5% Restriction, T4-Back to Standard Feed Intake, and T5-5% Overfed. All the treated groups are restricted at 25% during starter and vary only during grower stage. Two hundred male cobb broilers were distributed randomly to 5 treatments and replicated 4 times. Data on body weight, total weight gain, feed consumption, average daily gain, feed conversion ratio, broiler production index, and mortality rate were analyzed. Restricted-fed birds had significantly lower body weight and feed consumption at the starter stage but no significant effects on final body weight, total weight gain, and feed consumption during the grower stage. Moreover, no significant effects of restriction treatments on average daily gain and feed conversion ratio, however, restricted birds were more efficient in conversion than control during the starter stage. The restriction had no effect on the broiler production index and mortality rate, however, restricted-fed birds were more efficient in performance, cost of production, and harvest recovery. Since restricted-fed birds were slightly lighter than their assumed weight for age 35, full compensatory growth was not obtained. Restriction, on the other hand, resulted in improved performance by increasing feed utilization, harvest recovery, and lower production costs while preventing rapid growth